Recombinant amelogenin regulates the bioactivity of mouse cementoblasts in vitro - Sema S. Hakki; S. Buket Bozkurt; Emre Türkay; Michel Dard; Nuhan Purali; Werner Götz (Nature Publishing Group, 2018)
Regenerative medicine: Engineered amelogenin boosts oral cell activity A protein with its roots in dental development stimulates the proliferation and gene expression of cells linked to regeneration. Amelogenin is a mediator of enamel and tooth root formation, and the main component of a recently-developed medicine for periodontal regeneration. An international research group led by Sema Hakki, of Selcuk University, Turkey, has now elucidated the effects of amelogenin on cementoblasts, a type of cell responsible for producing the vital, mineralized layer on surface of the tooth root. Hakki's team found that the bacteria-derived amelogenin increased the rate of mouse cementoblast proliferation and mineralization in vitro, and increased the expression of genes related to bone and tissue generation. The team also demonstrated the presence of a likely amelogenin receptor on the cells used in their study. These findings support further investigation into amelogenin's therapeutic potential.